Investigation Stage of Social Education of Children and Young People with Disabilities in Poland and Ukraine - Perfileva, Majya (Pedagogical Discourse, 2013)
This article deals with the problem of historiographic analysis and generalization of Ukrainian and Polish researchers works concerning the study in the following areas: comparative studies; theoretical and methodological aspects of social education and socialization of individuals, special and Integrative learning; difficulties in cooperation with disabled children families; vocational rehabilitation and social protection. Despite the urgency of the problem in Polish society and many scientific investigations, the issue of social education of children and youth with disabilities still requires profound theoretical study of pedagogical principles of this process.